# Proving 1=2 and 2=3

• By: The DIG for Kids
• Time to read: 2 min.
Affiliate Disclaimer

As an affiliate, we earn from qualifying purchases including Amazon. We get commissions for purchases made through links in this post.

Mathematicians use mathematical proofs to prove that what they say about numbers is true. Some proofs look true but aren’t – these are known as fallacies. Here are a few fallacies:

## Proving 1=2

• Start by imagining that a = b
• Multiplying both sides by a, then a x a = a x b
• Adding (a x a) to both sides, then (a x a) + (a x a) = (a x a) + (a x b)
• This can be rewritten as 2(a x a) = (a x a) + (a x b)
• Subtracting 2(a x b) from both sides gives 2(a x a) – 2(a x b) = (a x a) + (a x b) – 2(a x b)
• Simplifying this gives 2(a x a) – 2(a x b) = (a x a) – (a x b)
• Factoring out the 2 on the left hand side gives 2((a x a) – (a x b)) = 1((a x a) – (a x b)
• Dividing both sides by ((a x a) – (a x b)) means that 2 = 1

What’s wrong? The final step cannot work because it is not possible to divide a number by zero, and if a = b, then (a x a) – (a x b) = 0.

## All Numbers are Equal

• When multiplying any number by zero, the answer is zero, so 1 x 0 = 0
• Rearranging this gives 1 = 0 / 0
• 2 x 0 = 0
• Rearranging this gives 2 = 0 / 0
• 3 x 0 = 0
• Rearranging this gives 3 = 0 / 0
• Therefore – all numbers are equal

What’s wrong? This cannot work because, as before, it is not possible to divide a number by zero.

## Making Four Equal 12

• Start by imagining that a = b
• Multiply both sides by four, so 4a = 4b
• Multiply both sides by 12, so 12a = 12b
• Multiply both sides of the first equation by a, so 4(a x a) = 4(a x b)
• Multiply both sides of the second equation by b, so 12(a x b) = 12(b x b)
• Subtract the second equation from the first equation to make one equation, so 4(a x a) – 12(a x b) = 4(a x b) – 12(b x b)
• Subtract 4(a x b) from both sides and add 12 (a x b) to both sides, so 4(a x a) – 4(a x b) = 12 (a x b) – 12 (b x b)
• Add a x b and subtract (b x b) from both sides, so 4(a x a) – 4(a x b) + (a x b) – (b x b) = 13 (a x b) – 13 (b x b)
• Taking (factoring) out common factors (dividing by (a-b)), so 4a(a – b) + b(a – b) = 13b(a – b)
• Taking (factoring) out common factors, so 4a + b = 13b
• Subtracting b from both sides, so 4a = 12b
• a = b, so substituting a for b, 4b = 12b, so therefore 4=12

What’s wrong? The step of dividing by (a – b) cannot work because it is not possible to divide a number by zero, and if a=b, then (a – b) = 0.